2004
DOI: 10.1115/1.1640357
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nonlinear Electro/Elastic Beam and Plate Systems (Finite Element Formulation and Analysis)

Abstract: Adaptive structures involving large imposed deformation often go beyond the boundary of linear theory and they should be treated as “nonlinear” structures. A generic nonlinear finite element formulation for vibration sensing and control analysis of laminated electro/elastic nonlinear shell structures is derived based on the virtual work principle. A generic curved triangular piezoelectric shell element is proposed based on the layerwise constant shear angle theory. The dynamic system equations, equations of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Secondly, the strain-stress relationship of PVDF and PPy films becomes nonlinear as the strain increases [22,23,29,30]. Thirdly, under large swelling, the symmetrical trilayer arrangement generates a neutral line that is no longer at the center line due to the geometric nonlinearity.…”
Section: Nonlinear Mechanical Model Based On a Swelling Frameworkmentioning
confidence: 99%
“…Secondly, the strain-stress relationship of PVDF and PPy films becomes nonlinear as the strain increases [22,23,29,30]. Thirdly, under large swelling, the symmetrical trilayer arrangement generates a neutral line that is no longer at the center line due to the geometric nonlinearity.…”
Section: Nonlinear Mechanical Model Based On a Swelling Frameworkmentioning
confidence: 99%
“…T HE active control of flexible structures has been an active field of research for several decades, and has played an important role in the incorporation of lightweight, lightly damped and inherently flexible designs for manipulator links, rotor blades, and aerospace structures (Narayanan and Balamurugan, 2003;Oliveira et al, 2004;Wang et al, 2004a;Hu and Ma, 2005;Wang and Mills, 2005;Vasques and Rodrigues, 2006). Lightweight designs have several advantages, such as high payload/weight ratio for power efficiency and fast maneuvering, in comparison to more massive, yet rigid, predecessors.…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al [8] numerically proved the thermopiezoelastic snapping phenomena of active piezolaminated plates based on multifield layerwise theories. Wang et al [9] reported adaptive structures involving large imposed deformation based on total Lagrangian formulation. Ahmad et al [10] formulated linear and nonlinear models of a smart beam using general electrothermoelastic relations.…”
Section: Introductionmentioning
confidence: 99%